Production, Diversity, and Distribution of Aquaculture Commodities in Tuban, Indonesia - Samara, Syifania Hanifah; Amin, Muhamad; Isroni, Wahyu; Hasan, Veryl; Santanumurti, Muhammad Browijoyo; Nugraha, Muhammad Ar Rozzaaq; Abualreesh, Muyassar H. (Faculty of Fisheries and Marine Universitas Airlangga, 2024)
Graphical Abstract Highlight Research Tuban (Indonesia) aquaculture commodities are surveyed. Aquaculture diversity in Tuban are consisted of 5 fields, namely rice field ponds, floating net cages, freshwater ponds, and brackish aquaculture ponds Aquaculture commodities in Tuban consist of 11 families and 14 species of the main aquatic production. Cyprinus carpio or common carp is one of the commodities cultivated in four different aquacultures. Abstract Fishery is a sector expected to overcome the food crisis. Indonesia is one of the leading countries in high volumes of fishery production in most of its areas, including the Regency of Tuban in East Java Province. The area of Tuban Regency is 1,839.94 km2 with the coastline covers 65 km and a sea area of 22,608 km2. This study aims to provide information regarding aquaculture production, diversity, and distribution in Tuban. This study used a survey method in collecting fishery commodity data directly from aquaculture areas. The results of this study showed that the highest production came from the brackish water with a value of 32.46% (13,561.79 tons), followed by rice field pond (27.79% or 11,612.45 tons), freshwater pond (25.76% or 10,764.62 tons), floating net cage (13.97% or 5,836.59 tons), and marine (0.1% or 5.67 tons). Aquaculture biodiversity in Tuban consisted of 11 families and 14 species of the main aquatic produces, such as Cyprinidae (Cyprinus carpio, Barbonymus gonionotus, Parastromateus niger), Clariidae (Clarias bathracus), Pangasiidae (Pangasianodon hypophthalmus), Penaeidae (Penaeus monodon, Litopenaeus vannamei), Channidae (Channa striata), Cichlidae (Oreochromis niloticus, Oreochromis mosammbicus), Osphronemidae (Osphronemus gourami), Serranidae (Epinephelus), Lutjanidae (Lutjanus), and Chanidae (Chanos chanos). Cyprinus carpio or common carp is fish cultivated in four different aquacultures, namely rice field pond, floating net cages, freshwater ponds, and brackish aquaculture ponds. Unfortunately, the diversity and production of marine aquaculture has not been improved even though Tuban has large marine areas.